DETEKSI BAKTERI RHIZOSFER KELAPA SAWIT DI TANAH MINERAL MENGGUNAKAN METODE PCR-RISA - Achmad Himawan; Hangger Gahara Mawandha (Program Studi Agroteknologi INSTIPER, 2018)
Oil palm (Elaeis guineensis Jack.) plantation is the biggest plantation in Indonesia. Indonesia is the biggest Crude Palm Oil (CPO) in the world since 2017. To maintain oil palm productivity is needed soil fertility research, especially rhizosphere bacteria. The aim of this research is to detect rhizosphere bacteria in mineral soil at oil palm plantation in Riau. Detection the bacteria used Polimerase Chain ReactionRibosomal Intergenic Spacer Analysis (PCR-RISA) method. The research result showed that there is one bacterium species in the mineral soil. Keywords: rhizosphere bacteria, oil palm, mineral soil, PCR-RISA